Entrepreneurial orientation of rural business holders (micro and small): Evidence from industrialized suburbs of an emerging economy - Abeywardana, T.; Gangadhara, K.R.; Dilhani, K.S. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Micro and small-scale ventures are known to be vital vectors for eradication of poverty and uplifting the livelihood of the community. Entrepreneurial orientation in three dimensions – proactiveness, innovativeness and risk-taking ability – provide insights into the entrepreneurial behaviour of business operators. The present research is focused on the entrepreneurial orientation of business owners in a turbulent environment in regard to their business performance. The quantitative research was carried out with 92 businesses in the industrialised zone of Sri Lanka. The findings revealed that, in a changing environment, the most vigilant EO dimension is risk-taking ability. In-depth analysis of risk-taking ability indicated that micro and small entrepreneurs on highly competitive platforms do not tend to pursue highrisk projects. Thus, it can be concluded that entrepreneurs in turbulent environments take calculated risks to thrive in their businesses.
Keywords: Entrepreneurial orientation, rural business, risk-taking ability, Sri Lanka